2009
DOI: 10.2136/sssaj2008.0205
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Estimation of Soil Total Nitrogen Using Cokriging with Predicted Soil Organic Matter Content

Abstract: Accurate measurement of soil total N (TN) content in agricultural fields is important to guide reasonable application of nitrogenous fertilizer. Estimation of soil TN content with limited in situ data at an acceptable level of accuracy is important because laboratory measurement of N is a time‐ and labor‐consuming procedure. This study was conducted to evaluate cokriging of soil TN with predicted soil organic matter (SOM) content as auxiliary data. The SOM content was predicted by cokriging with a digital numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The estimation of non-sampled points through co-kriging was described by Yamamoto and Landim (2013), among others, which is an extension of kriging, where one or more easier measured variables help to explain the target variable as they are correlated (Wu et al, 2009). For this approach, the identification of the neighbors' weight was made with the fitted parameters of the crossed semivariogram.…”
Section: Ordinary Kriging and Co-krigingmentioning
confidence: 99%
“…The estimation of non-sampled points through co-kriging was described by Yamamoto and Landim (2013), among others, which is an extension of kriging, where one or more easier measured variables help to explain the target variable as they are correlated (Wu et al, 2009). For this approach, the identification of the neighbors' weight was made with the fitted parameters of the crossed semivariogram.…”
Section: Ordinary Kriging and Co-krigingmentioning
confidence: 99%
“…Note that the four experimental configurations (A–D) are designed to illustrate the effect of the SOM prediction accuracies when different combinations of spectral bands have been used for the analysis. Specifically in experiment (D), where only the SOM featured bands have been selected like that of the traditional method commonly adopted by workers in the field [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], the experiment is designed to compare the impacts when SOM only bands are utilised with respect to the proposed band selection method as set out in Experiment (C).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the correction approach as outlined in the previous paragraph, alternative methodology has been the discovery of the SOM related spectral bands [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] particularly those which are not greatly affected by the absorption feature of moisture in the soil [ 60 , 61 , 62 ]. There are numerous reports about the SOM-related absorption features in the vis-NIR spectral range and studies have revealed that spectral bands in the 800–1400 nm, 1600–1700 nm, 2100–2200 nm and 2300–2500 nm region [ 61 ] are relatively free of interference because of the presence of moisture content in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, weight was obtained with the parameters of the semivariogram fitted for the characteristic being evaluated (HT). The estimation of unsampled points made from co-kriging was described by Yamamoto and Landim (2013), among other authors, and is an extension of kriging, in which one or more easy-tomeasure variables helps explain a difficult-to-measure primary variable (Wu et al, 2009). For this approach, the identification of weights was obtained with the parameters of crossed semivariance fitted for the variable HT, where the secondary variable was the DBH, which was obtained for all the individuals in the stand.…”
Section: Spatial Prediction Models -Ordinary Kriging and Co-krigingmentioning
confidence: 99%